Factors Influencing Convenience Stores Survival in Response to New Normal Lifestyles - Sodsup, Kullatada; Sirisopana, Somchawee (Interdisciplinary Academic and Research Journal, 2023)
Convenience stores are facing various difficulties from the current business environment, such as an increase in competition, transformation into the technology era, and shifts of consumer behavior into the new normal lifestyles as a result of the COVID-19 crisis. Therefore, convenience store businesses must seek ways to adjust themselves to survive under such hard conditions. The objective of this research was to examine the factors affecting the survival of convenience stores in response to the new normal lifestyles. The questionnaire was used as a tool in this quantitative research. The research samples were 400 convenience store employees in Bangkok which were selected by using convenience sampling. The collected data were analyzed by using frequency, percentage, mean, standard deviation, and multiple regression analysis. The results showed that the opinions of these convenience store employees on the transformational leadership factor were at a high level. On the other hand, their opinions on digital transformation, knowledge management, and survival of convenience stores in response to the new normal lifestyles were at the highest level. The results of the hypothesis testing revealed that the factors affecting the survival of convenience stores in response to the new normal lifestyles were: Transformational Leadership (β = .280), Digital Transformation (β = .408), and Knowledge Management (β = .471). Each of these three factors influenced the survival of convenience stores in response to the new normal lifestyles at the 0.01 level of statistical significance. The model had a coefficient of determination value of .717, meaning that it could explain 71.7 percent of the variability in the survival of convenience stores in response to the new normal lifestyles.